(3OjhGf CHj aQGS GdMeOGfjs - (3CHh aQGS , GdMGQK Hf SYjO Hf MeOGf GdJZdHj GdQHYj, CHhaQGS GdMeOGfj,J (B357 (3g` s ((3jMji Hf Ydj Hf EHQGgje Hf egOj s)
(3ChdgG (B:s
(3ef bGajg GdCda(B: (3Ye UHGMkG hEf ZOhJ NdGA ef XHGA jaVMfj ajc GdXHGA s
(3BNQgG (B:s
(3ef CQLhRI aj GdWQO(B: (3hde fRd SHY djGmd YOOG CSYnO ef QGM aGSXj ef ZOG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI KGfjIs
(3QhGjI GHf NGdhjgs
(3hQO CjVkG JMJ Qbe (B475s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs